2020
DOI: 10.1096/fj.201902964r
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exosomal miRNAs involved in endothelial injury in microscopic polyangiitis patients

Abstract: Microscopic polyangiitis (MPA) is a systemic autoimmune disease that primarily affects the small and medium blood vessels. Endothelial injury is one of the pathological hallmarks of MPA. However, the pathogenesis for this has not yet been fully elucidated. Exosomal microRNAs (miRNAs) have recently emerged as a new molecular pattern involved in the endothelial injury in other diseases. Hence, we speculated that MPA plasma-derived exosomes (MPA-exo) could induce the endothelial injury, which was likely to be aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Similar to other types of cells, vascular endothelial cells have the ability to produce and take up exosomes. Therefore, circulating exosomes may be captured by vascular endothelial cells throughout the body and cause cell injury, which may contribute to the various pathophysiologies of organs in the above-described diseases and MPA ( Gao et al, 2021 ; Roig-Carles et al, 2021 ; Wang et al, 2020 ). In the current study, we observed that exosomes isolated from the plasma of MPA patients and HC could be absorbed into HUVEC via endocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other types of cells, vascular endothelial cells have the ability to produce and take up exosomes. Therefore, circulating exosomes may be captured by vascular endothelial cells throughout the body and cause cell injury, which may contribute to the various pathophysiologies of organs in the above-described diseases and MPA ( Gao et al, 2021 ; Roig-Carles et al, 2021 ; Wang et al, 2020 ). In the current study, we observed that exosomes isolated from the plasma of MPA patients and HC could be absorbed into HUVEC via endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are nanometre-sized microvesicles secreted by almost all mammalian cell types and range in size from 30 to 150 nm. Increasing evidence suggests that exosomes are abundant in biological fluids, including serum, and circulate with the fluids, facilitating communication between various cells and their microenvironment ( Prikryl et al, 2020 ; Surmiak et al, 2021 ; Wang et al, 2020 ). Exosomes deliver bioactive molecules, such as mRNA, microRNA (miRNA), long noncoding RNA, proteins, and lipids, from parental cells to recipient cells, playing an important role in many diseases, including cancer, AAV, and acute kidney injury ( Dong et al, 2019 ; Huang et al, 2020 ; Oh & Kwon, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qianjin Lu and Ming Zhao co-published 4 papers, two of which reviewed the research progress of exosomes in the pathogenesis, immune regulation and treatment of AIDs (53,58), and the two other articles pointed out the mechanism of serum exosomal miR-451a and miR-642-3p involved in the pathogenesis of SLE and SS (59,60). Wei Wei published 4 papers, three of which reviewed the pathogenesis of extracellular vesicles in vasculitis and lupus nephritis (LN) (61)(62)(63), and another article pointed out plasma exosomes participate in the inflammation process of microscopic polyangiitis (64). Besides, four papers authored by Jim Xiang mainly studied the immunomodulatory effects of exosomes derived from CD4 + T cells, CD8 + 25 + regulatory T cells (65-67) and dendritic cells (68) in mice.…”
Section: General Informationmentioning
confidence: 99%
“…More recently the association of platelet-related miRNAs was studied in ACS patients on DAPT and pathophysiological processes in the TDM population [ 16 , 19 , 20 , 21 , 22 , 23 ]. Among others, Let-7e and miR-125a-3p are molecules that have been formerly linked to inflammation, platelet reactivity, and mechanisms leading to diabetes; however, the impact of antiplatelet therapy on Let-7e and miR-125a-3p and their prognostic potential has not been studied so far [ 24 , 25 , 26 ]. Therefore, our aim was to analyze the impact of antiplatelet treatment on Let-7e and miR-125a-3p expressions and confirm the previous observations for miR-126 and miR-223 expressions, as well as investigate their usefulness as predictive biomarkers specifically in the T2DM cohort.…”
Section: Introductionmentioning
confidence: 99%